Ecomotion Cityglide Commuter E-Bike - Abhinav Appu; Akash Vijayan; Noufiya N; Akhil A.G (International Journal of Mechanical Dynamics and Systems Analysis, 2024)
The transition from conventional gasoline motorcycles to electric bikes represents a pivotal step in addressing the increasing demand for sustainable transportation solutions in urban environments. This paper meticulously explores the multifaceted aspects of this transition, focusing on the technological advancements, design innovations, and societal implications associated with the adoption of electric bikes. Electric bikes, powered by Brushless DC (BLDC) motors and rechargeable battery packs, offer a suite of benefits over their gasoline counterparts. Notably, they contribute to diminished pollution levels, reduced maintenance requirements, and quieter operation, aligning with the imperative to mitigate environmental impact and improve urban air quality. Leveraging advancements in battery technology, electric bikes boast extended ranges and faster charging times, enhancing their practicality for daily commuting and recreational use. At the core of the project lies the development of a sophisticated distribution system for electric bike batteries. This system aims to facilitate seamless battery charging and recharging, ensuring optimal performance and user convenience. By establishing a network of charging stations strategically placed throughout urban areas, users can easily access reliable charging infrastructure, thereby alleviating range anxiety and promoting widespread adoption of electric bikes. In terms of design innovation, electric bikes feature a foldable structure, enhancing their portability and versatility across diverse usage scenarios. This transformative design element not only streamlines storage and transportation but also enhances accessibility for users, catering to the needs of urban commuters and recreational riders alike. Furthermore, the integration of a robust security system augments user confidence by safeguarding the bikes during storage or transit, addressing concerns related to theft and vandalism. Complementing the physical design enhancements, electric bikes are equipped with a top mounted screen that provides riders with essential real-time data, including speed, distance traveled, and battery status. This interactive interface empowers riders with greater control and insight into their riding experiences, enhancing overall safety and user satisfaction. Additionally, the incorporation of advanced sensors, such as those for speed and distance, underscores a commitment to safety, ensuring optimal road-sharing practices and minimizing the risk of accidents. Through a meticulous blend of sustainability, convenience, and safety features, electric bikes are poised to revolutionize urban transportation landscapes. By offering a viable alternative to traditional gasoline motorcycles and cars, electric bikes contribute to reducing traffic congestion, lowering carbon emissions, and promoting healthier lifestyles. As cities worldwide grapple with the challenges of urbanization and environmental degradation, the widespread adoption of electric bikes emerges as a promising solution for building greener, more accessible, and more resilient urban environments.
Keywords: BLDC Motor; Conserving energy; Electricity; e-bikes; rechargeable battery